What affects China’s high-tech industry land misallocation: Government behavior or enterprise behavior? - Han, Lu; Zhou, Liping; Bao, Haijun; Zeng, Xin; Taghizadeh-Hesary, Farhad (Frontiers in Environmental Science, 2022)
The high-tech industry belongs to the core strategic national development category and is essential in promoting social future economic growth and scientific and technological progress. This paper constructs a theoretical framework for high-tech industry land misallocation based on the four-level institutional analysis method. The study selects Zhejiang Province of China as the research area. It uses the litera-ture research method and multiple regression analysis methods to analyze the root causes and influence mechanism of land misallocation for the high-tech industry. The research shows that the land-use support policies for the high-tech industry can effectively alleviate the misallocation of land factors. In contrast, the government's improper financial support measures and tax incentives will increase the degree of land misallocation in the high-tech industry. The higher the R&D expenditure-to-income ratio and profitability, the less land misalloca-tion will occur in the high-tech industry. Government behavior and enterprise behavior impact land misallocation in the high-tech industry, but government behavior has a major impact. Therefore, the government, enterprises, and the market should adopt an integrated strategy to reduce excessive government intervention in land resource allocation, allowing the market to play a decisive role in resource allocation, and stimulate the vitality of enterprise R&D and innovation. This study helps to reveal the deep motivation of land misallocation for high-tech industry and provides practical guidance for optimizing the high-tech industrial land allocation and promoting high-quality industrial development.